Recurrence and Survival After Resection of Small Intraductal Papillary Mucinous Neoplasm-associated Carcinomas (⩽20-mm Invasive Component): A Multi-institutional Analysis. Issue 4 (April 2016) - Winter, Jordan M.; Jiang, Wei; Basturk, Olca; Mino-Kenudson, Mari; Fong, Zhi Ven; Tan, Wei Phin; Lavu, Harish; Vollmer, Charles M.; Furth, Emma E.; Haviland, Dana; Klimstra, David S.; Jarnagin, William R.; et al.
Abstract : Background: Early invasive carcinoma may be encountered in association with intraductal papillary mucinous neoplasms (IPMNs) of the pancreas. The natural history of these early invasive lesions is unknown. Methods: Pancreatic surgical databases from 4 high-volume centers were queried for IPMNs, with invasive components measuring 20 mm or less. All cases were reviewed by GI gastrointestinal pathologists, and pathologic features were analyzed to identify predictors of recurrence and survival. Results: A total of 70 small IPMN-associated invasive carcinomas (⩽20-mm invasion) were identified, comprising 25% of resected IPMN-associated carcinomas (n = 280). Most of these small invasive cancers were multifocal (66%), less than 10 mm in size (73%), and arose in the setting of a main duct IPMN (96%). The most common adenocarcinoma subtypes were tubular (57%) and colloid (29%). Lymph node metastases were present in 19% of cases and 23% were T3 lesions. The overall recurrence rate was 24% (n = 17), and the median time to recurrence was 16 months (range: 4–132 months). Median and 5-year survival rates were 99 months and 59%. Recurrence patterns of invasive disease were local in 35%, distant in 47%, and both in 18%. Lymphatic spread and T3 stage were predictive of recurrence (univariate, P = 0.006), whereas tubular carcinoma type was the most predictive of poor overall survival (multivariate hazard ratio = 3.7, P = 0.04). Conclusions: This study represents the largest multi-institutional experience of resected small IPMN-associated carcinoma. Although these malignancies may frequently be cured with resection, recurrence risk is significant. Lymphatic spread, increased T stage, and tubular type carcinoma were associated with the poorest outcome. Abstract : Supplemental Digital Content is available in the text